Analyzing the Environmental Kuznets Curve Hypothesis in terms of Airplane Transport: Empirical Examination for Baltic States - Bahadır, Seda (International Journal of Energy Economics and Policy, 2022)
The main goal of this paper is to investigate the long-term nexus among energy consumption, economic growth, civil aviation, and CO2 emissions by performing the ARDL, DOLS and Panel data analysis for Baltic countries including Estonia, Finland, Latvia, and Lithuania from 1992 to 2021 within the context of EKC hypothesis. The long-term ARDL and DOLS models result indicate that there is a statistically significant relationship between the air transport, CO2, GDP, and energy consumption for Estonia from 1992 to 2021. On the other hand, the impact of independent variables containing air transport, GDP, and energy consumption on CO2 emission is demonstrated empirically from 1992 to 2021 which is affirmed the EKC hypothesis for Baltic countries through panel data analysis. According to empirical findings, legal arrangements should be made for the production and use of alternative fuels by policy makers in order to provide economic and social benefits in terms of reduction environmental pollution. Low-emission fuels and hybrid or electric vehicles must be used to reduce carbon dioxide emissions as a solution for environmental degredation in Baltic countries.